Therapeutic JAK1 Inhibition Reverses Lupus Nephritis in a Mouse Model and Demonstrates Transcriptional Changes Consistent With Human Disease - Rachel E. Twomey; Stuart J. Perper; Susan V. Westmoreland; Swetha Srinivasan; Suzanne L. Mathieu; Kristine E. Frank; Jozsef Karman; Andrew J. Long; William J. Housley; Stephen H. Clarke (ACR Open Rheumatology)
Objective Janus kinase family members are essential for signaling by multiple cytokines, including many implicated in systemic lupus erythematosus (SLE) pathogenesis. To test whether inhibition of JAK1 signaling can be efficacious in SLE, we used a JAK1‐selective inhibitor (ABT‐317) and evaluated its ability to ameliorate disease in murine SLE. Methods Efficacy of ABT‐317 was evaluated using NZB/W‐F1 mice treated prophylactically and therapeutically. Primary endpoints were proteinuria, survival, and saliva production. Other endpoints included histological analysis of kidneys and salivary glands, flow cytometric analysis of splenic cell populations, and gene expression analysis by RNA sequencing in the kidneys, salivary glands, and blood. Publicly available human kidney gene transcription data were used to assess the translatability of the mouse findings. Results ABT‐317 was efficacious when dosed prophylactically and prevented disease for up to two months after treatment cessation. When dosed therapeutically, ABT‐317 quickly reversed severe proteinuria and restored saliva production, as well as diminished kidney and salivary gland inflammation. ABT‐317‐induced changes in glomerular morphology coincided with normalization of a human nephrotic gene signature, suggesting translatability to human lupus nephritis (LN). Conclusion JAK1 inhibition prevented and reversed kidney and salivary gland manifestations of murine lupus with long‐lasting effects after treatment cessation. These data, along with the presence of JAK1 and nephrotic gene signatures in human LN glomeruli, suggest that a JAK1‐selective inhibitor may be an effective therapeutic in the treatment of human SLE and LN.